Inditex group equity research - dcf approach - Carvalho, Ana Maria Monteiro (2021)
This dissertation aims to assess the equity value of a listed company combining academic theory with appropriate valuation practices. The chosen company was Inditex, one of the main players in the Apparel sector around the world. Several reasons motivated this choice. First, Inditex has developed a unique business model, highly responsible for its differentiation and success on the market. It is characterized by its responsiveness, flexibility, and customer-orientation. Furthermore, the Group is currently facing a delicate situation, mainly due to the temporary closure of its stores as a consequence of the Covid-19 pandemic. In addition to a decrease in sales, the company’s business model and the ability to respond effectively to external adversities were put under pressure. These factors added up to an interesting valuation challenge. An analysis of the Apparel Industry and the company’s business was carried out to determine its value. Considering Inditex’s characteristics, the Discounted Cash Flow method was considered the most reliable approach. In the end, a final target share price of 29,90€ was computed. In comparison with the current market price (26,04€ per share), the DCF model indicated that Inditex’s stock price was slightly undervalued. Thus, there is up side potential to the price of its shares, translated into a buy recommendation.